Women as global leaders - Ngunjiri, Faith Wambura, 1973-; Madsen, Susan R. (Women and leadership (Charlotte, N.C.), 2015)
Women as Global Leaders is the second volume in the new Women and Leadership: Research, Theory, and Practice book series published for the International Leadership Association by IAP. Global leadership is an emerging area of research, with only a small but growing published literature base. More specifically, the topic of women's advances and adventures in leading within the global context is barely covered in the existing leadership literature. Although few women are serving in global leadership roles in corporate and non-profit arenas, and as heads of nations, that number is growing (e.g., Indira Nooyi at PepsiCo, Sheryl Sandberg at Facebook, Marissa Mayer at Yahoo, Ellen Johnson Sirleaf as president of Liberia, Angela Merkel as chancellor of Germany).The purpose of this volume is to provide the reader with current conceptualizations and theory related to women as global leaders, recent empirical investigations of the phenomenon, analysis of effective global leadership development programs, and portraits of women who lead, or have led, in a global role. The volume is divided into four sections. The first section covers the state of women as global leaders, containing chapters by Joyce Osland and Nancy Adler, pioneers in the field of global and/or women's leadership. The second section describes approaches to women's global leadership. The third section offers an analysis of programs that are useful in developing women as global leaders, with the final section profiling women as global leaders, including Margaret Thatcher, Nobel Laureate Malala Yousfazai, and Golda Meir. As Barbara Kellerman noted in the Foreword, "this book... should be understood as a collection whose time has come, precisely because women now have opportunities to lead that are far more expansive than they were even in the recent past. Though their numbers remain low, they are able in some cases to exercise leadership not only as outsiders, but also as insiders, from the very positions of power and authority to which men forever have had access."